Dakwah pada Masyarakat Marginal Perkotaan (Studi Kasus Kota Padang) - Mahmuda, Mardan; Bukhari, Bukhari (Fakultas Dakwah dan Ilmu Komunikasi, 2020)
Abstract: Da'wah activities should be able to attract attention and be able to be a surefire alternative for marginalized communities to solve their life problems, especially problematics on economic aspects. In other words,